P1-S6.20 Perinatal Screening for STIs in the USA: adherence to preventive screening recommendations for HIV and syphilis among the commercially insured (2008). (10th July 2011) - Janes, G; Beard, A; Tao, G; Hoover, K; Kent, C
Abstract : Background: Perinatal transmission of sexually transmitted infections is a preventable source of morbidity. In the USA, the incidence of congenital syphilis has increased by 23% since 2005 and, in 2008, 141 infants were infected with HIV, despite the fact that the CDC recommends routine prenatal syphilis and HIV screening. To encourage compliance with guidelines, many payers rely on claims data to track utilisation. In this study, the percentage of women screened for syphilis or HIV during their pregnancy was estimated using MarketScan claims data, as a measure of compliance and of the feasibility of using these data for assessment of prenatal screening. Methods: We analysed data from the MarketScan database, that allows linkage of de-identified patient and utilisation data from varying sites of care. The analysis was restricted to women who delivered a live birth in 2008, and who were continuously enrolled in one health plan for at least 293 days prior to delivery. The eligible population was identified using the coding algorithm for a live birth defined by HEDIS. Results: Among the 220 571 women with a live birth in 2008, 87.0% received a syphilis test during their pregnancy, 74.1% received an HIV test and 73.3% received both. The test rate for syphilis was highest for those 31–35 yrs (88.2%) and lowest for those 15–20 yrs (78.3%). The test rate for HIV was highest among those 21–25 yrs (75.2%) and lowest among those 15–20 yrs (70%). Both prenatal syphilis and HIV test rates were highest among those insured by a preferred provider plan. Regionally, testing rates were highest in the South (89.8% for syphilis and 82.1% for HIV) and lowest in the Northeast for syphilis (82.8%) and in the West for HIV (62.9%). Conclusions: The results suggest fairly good compliance with guidelines for prenatal HIV and syphilis screening, although utilisation still varies by age, insurance type and geographic region. The MarketScan database represents individuals covered by employment-based health plans, which is how most Americans are insured. These data provide a unique opportunity to assess utilisation among the insured, at a time when the USA is poised to move a larger proportion of the population into this group. Tracking of year-to-year changes could help public health and healthcare organizations partner to improve care and target interventions to ensure equal access to these critical services.